A 12-wk whole-grain wheat intervention protects against hepatic fat: the Graandioos study, a randomized trial in overweight subjects - Schutte, Sophie; Esser, Diederik; Hoevenaars, Femke P M; Hooiveld, Guido J E J; Priebe, Marion G; Vonk, Roel J; Wopereis, Suzan; Afman, Lydia A (The American journal of clinical nutrition, 2018)
Whole-grain wheat (WGW) is described as nutritionally superior to refined wheat (RW) and thus advocated as the healthy choice, although evidence from intervention studies is often inconsistent. The liver, as the central organ in energy metabolism, might be an important target organ for WGW interventions. The aim of this study was to investigate the potential benefits of WGW consumption compared with RW consumption on liver health and associated parameters. We performed a double-blind, parallel trial in which 50 overweight 45- to 70-y-old men and postmenopausal women were randomly allocated to a 12-wk intervention with either WGW (98 g/d) or RW (98 g/d) products. Before and after the intervention we assessed intrahepatic triglycerides (IHTGs) and fat distribution by proton magnetic resonance spectroscopy/magnetic resonance imaging, fecal microbiota composition, adipose tissue gene expression, and several fasting plasma parameters, as well as postprandial plasma lipids after a mixed meal. Fasting plasma cholesterol, triglycerides, nonesterified fatty acids, and insulin were not affected by RW or WGW intervention. We observed a substantial increase of 49.1% in IHTGs in the RW when compared with the WGW group (P = 0.033). Baseline microbiota composition could not predict the increase in IHTGs after RW, but gut microbiota diversity decreased in the RW group when compared with the WGW group (P = 0.010). In the WGW group, we observed increased postprandial triglyceride levels compared with the RW group (P = 0.020). In addition, the WGW intervention resulted in a trend towards lower fasting levels of the liver acute-phase proteins serum amyloid A (P = 0.057) and C-reactive protein (P = 0.064) when compared to the RW intervention. A 12-wk RW intervention increases liver fat and might contribute to the development of nonalcoholic fatty liver disease, whereas a 12-wk 98-g/d WGW intervention prevents a substantial increase in liver fat. Our results show that incorporating feasible doses of WGW in the diet at the expense of RW maintains liver health. The study was registered at clinicaltrials.gov as NCT02385149.